PsycEXTRA Dataset 2003
DOI: 10.1037/e688902011-001
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Time: Family and Child Factors Associated with Self-Care

Abstract: to be published as part of Assessing the New Federalism, a joint project of Child Trends and the Urban Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(65 citation statements)
references
References 6 publications
2
61
1
1
Order By: Relevance
“…Although the rate of young children being left home alone seems low, it is and would be expected to be low in comparison to the high-risk families enrolled in the home visiting program in Hawaii discussed earlier (Duggan et al, 2004). However, the rates reported by mothers of older children are consistent with the findings from the National Survey of America's Families analyzed by Vandivere, Tout, Zaslow, Calkins, and Capizzano (2003): 7% of 6-to 9-year-olds and 25% of 9-to 12-year-olds were left home alone for periods, designated as "self-care". In addition, 3% of households were considered "food insecure with hunger" at any time in the month prior to the national survey conducted by the U.S. Department of Agriculture (Nord, Andrews, & Carlson, 2005), compared to 2% of households in our study indicating that they were unable to provide enough food at least once in the month prior to being surveyed.…”
Section: Discussionsupporting
confidence: 83%
“…Although the rate of young children being left home alone seems low, it is and would be expected to be low in comparison to the high-risk families enrolled in the home visiting program in Hawaii discussed earlier (Duggan et al, 2004). However, the rates reported by mothers of older children are consistent with the findings from the National Survey of America's Families analyzed by Vandivere, Tout, Zaslow, Calkins, and Capizzano (2003): 7% of 6-to 9-year-olds and 25% of 9-to 12-year-olds were left home alone for periods, designated as "self-care". In addition, 3% of households were considered "food insecure with hunger" at any time in the month prior to the national survey conducted by the U.S. Department of Agriculture (Nord, Andrews, & Carlson, 2005), compared to 2% of households in our study indicating that they were unable to provide enough food at least once in the month prior to being surveyed.…”
Section: Discussionsupporting
confidence: 83%
“…In MENA, ESA, and WCA, both positive and negative associations with socioeconomic status coexist for children home alone. Analyses with national data in the U.S. show that being home alone is more common in upper-income families [32,37,48], even if few children aged 5–7 years are home alone regardless of their income level [36] and children from both low- and high-income groups spend about the same amount of time home alone [32]. This may be partly explained by richer families’ higher likelihood to live in neighborhoods perceived as safe [36].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, such as the child’s sex, maternal education, household income, and the presence of other adults and children in the household, [32,33] do not consistently increase the likelihood of children being home alone [32,34]. Thus, some studies have found that boys are slightly more likely than girls to be home alone, yet this association was not significant for all age groups [32,35]. Similarly, some evidence has shown that higher maternal education is associated with a higher likelihood of children being home alone, particularly when the mother has at least a college degree [32,35], yet this association does not hold for children over nine years of age [36].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations